Membangun Pendidikan Berwawasan Gender - Syaefudin Achmad (Yinyang: Jurnal Studi Islam Gender dan Anak, 2019)
The role of women in national development is increasingly significant and should not be underestimated. To build human resources for women, education is needed that upholds gender equality so that their rights to education can be realized. But inevitably, education in Indonesia in its history has experienced a dark period where women lacked rights in education. There was once a gender gap in the world of education in Indonesia. There are several factors that influence it, such as community culture and school structure systems that lack opportunities for women to take part. Therefore, gender-conscious education needs to be realized in order to address the gender issue. One effort to realize gender-oriented education can be by developing a gender-sensitive learning process approach through fostering and training teachers, principals, and education supervisors, as well as at the level of decision making in all national education management units.